After the war is over : a novel - Robson, Jennifer, 1970- (William Morrow, an imprint of HarperCollinsPublishers, 2015)
"After four years as a military nurse, Charlotte Brown is ready to leave behind the devastation of the Great War. The daughter of a vicar, she has always been determined to dedicate her life to helping others. Moving to busy Liverpool, she throws herself into her work with those most in need, only tearing herself away for the lively dinners she enjoys with the women at her boarding house. Just as Charlotte begins to settle into her new circumstances, two messages arrive that will change her life"--Amazon.com.